Pemanfaatan Limbah Pertanian sebagai Material Akustik Ramah Lingkungan - Dady sulaiman; Siti Maria Ulva (Jurnal Teori dan Aplikasi Fisika, 2025)
Indonesia is an agricultural country, where agriculture as a national income source. Therefore, Indonesia produces a large amount of agricultural waste, that is still underutilised. Agricultural waste can be used in various ways, one of which is as an acoustic material. Acoustic materials can absorb sound and reduce noise pollution. This study aims to determine the factors that affect the sound absorption coefficient of acoustic materials. This study uses the literature review method by taking literature sources from different scientific journals. The literature sources used in this study consist of national and international journals from the last five years (2019–2023). This study refers to previous research data explores natural materials that have the potential to become acoustic materials. Based on the literature review,the natural materials that have the potential to become acoustic materials are sawdust, sugarcane, cassava, and rice husk. These materials can be considered for further research by changing independent variables such as density, thickness, and type of adhesive. In Addition, further research can also combine different materials with other natural fibres. Keywords: natural fibers, waste utilization, agro-waste, acoustic material, sound absorption coefficient.